Representations of the Israeli-Palestinian conflict on Twitter: a corpus-based linguistic analysis - Rehab Hassan Mahmoud (Insights into Language, Culture and Communication)
The present study aims not only to linguistically analyze the tweets produced in relation to the Israeli-Palestinian conflict from October 7th to 30th in 2023, which is the first twenty-three days of the conflict, but also to present a multi-layered analysis of the linguistic elements in the selected tweets. It also investigates the representations of the conflict in 475 tweets of a number of Western public figures and international organizations, which were analyzed in a quantitative and qualitative study design. The study employs a triangulation of three theoretical frameworks; namely, Halliday’s (2014) framework of Systemic Functional Linguistics, Fairclough’s (1989) three-dimensional Model of Critical Discourse Analysis, and van Dijk’s (1993) socio-cognitive framework of ingroup and outgroup representation. In a corpus-based approach, the study explores the frequency of not only conflict-related lexical elements, but also their two- or three-word clusters in the selected tweets by using a software programme; that is, AntConc (3.5.7, 2018), which helps identify the key words and clusters which are frequently used and distributed in the tweets. Results demonstrate a preponderant use of a number of words as well as two- or three-word clusters related to Israel, Hamas, Gaza, etc which not only contribute to the writer’s construction of meaning, but also present the West’s support towards Israel’s military operations in Gaza. Received on: 25 March 2025 Accepted on: 04 April 2025 Published on: 22 April 2025